How to write book reports - Teitelbaum, Harry (New York Monarch Press, 1975)
An introduction to the techniques of writing book reports and reviews, including how to read correctly, note taking, topic limitation, outlining, sample introductions, checklists, and suggested topics.
Keywords: English language -- Rhetoric; Book reviewing; Book reviewing; Report writing; Report writing